Atypical CXCL12 signaling enhances neutrophil migration by modulating nuclear deformability - Calì, Bianca; Deygas, Mathieu; Munari, Fabio; Marcuzzi, Elisabetta; Cassará, Antonino; Toffali, Lara; Vetralla, Massimo; Bernard, Mathilde; Piel, Matthieu; Gagliano, Onelia; Mastrogiovanni, Marta; Laudanna, Carlo; et al. (Science signaling, 2022)
To reach inflamed tissues from the circulation, neutrophils must overcome physical constraints imposed by the tissue architecture, such as the endothelial barrier or the three-dimensional (3D) interstitial space. In these microenvironments, neutrophils are forced to migrate through spaces smaller than their own diameter. One of the main challenges for cell passage through narrow gaps is the deformation of the nucleus, the largest and stiffest organelle in cells. Here, we showed that chemokines, the extracellular signals that guide cell migration in vivo, modulated nuclear plasticity to support neutrophil migration in restricted microenvironments. Exploiting microfabricated devices, we found that the CXC chemokine CXCL12 enhanced the nuclear pliability of mouse bone marrow-derived neutrophils to sustain their migration in 3D landscapes. This previously uncharacterized function of CXCL12 was mediated by the atypical chemokine receptor ACKR3 (also known as CXCR7), required protein kinase A (PKA) activity, and induced chromatin compaction, which resulted in enhanced cell migration in 3D. Thus, we propose that chemical cues regulate the nuclear plasticity of migrating leukocytes to optimize their motility in restricted microenvironments.